Degradation and osteogenic induction of a SrHPO4-coated Mg–Nd–Zn–Zr alloy intramedullary nail in a rat femoral shaft fracture model. (July 2020) - Wang, Zhe; Wang, Xinyuan; Tian, Yuan; Pei, Jia; Zhang, Jian; Jiang, Chang; Huang, Junming; Pang, Zhiying; Cao, Yuanwu; Wang, Xiuhui; An, Senbo; Wang, Xiao; et al.
Abstract: Magnesium and Mg-based alloys are promising biomaterials for orthopedic implants because of their degradability, osteogenic effects, and biocompatibility. However, the drawbacks of these materials include high hydrogen gas production, unexpected corrosion resistance, and insufficient mechanical strength duration. Surface modification can protect these biomaterials and induce osteogenesis. In this work, a SrHPO4 coating was developed for our patented biodegradable Mg–Nd–Zn–Zr alloy (abbr. JDBM) through a chemical deposition method. The coating was characterized by in vitro immersion, ion release, and cytotoxicity tests, which showed a slower corrosion behavior and excellent cell viability. RNA sequencing of MC3T3E1 cells treated with SrHPO4 -coated JDBM ion release test extract showed increased Tlr4, followed by the activation of the downstream PI3K/Akt signaling pathway, causing proliferation and growth of pre-osteoblasts. An intramedullary nail (IMN) was implanted in a femoral fracture rat model. Mechanical test, radiological and histological analysis suggested that SrHPO4 -coated JDBM has superior mechanical properties, induces more bone formation, and decreases the degradation rate compared with uncoated JDBM and the administration of TLR4 inhibitor attenuated the new bone formation for fracture healing. SrHPO4 is a promising coating for JDBM implants, particularly for long-bone fractures. Highlights: SrHPO4 reduces the in vivo corrosion rate of Mg–Nd–Zn–Zr implants. Release of Sr 2+ and Mg 2+ ions induces a biochemical response in rat femur fracture model. Osteogenic response is stimulated by the TLR4/PI3K/Akt signaling pathway. Improved mechanical stability and osteogenic induction enhances fracture healing.